Rankings achievement 2023: UiTM's Art and Design Subject Ranked in 2023 QS World University Rankings by Subject - UiTM, UiTM Global (Office of International Affairs (OIA), 2023)
22 March 2023 Results of the QS World University Rankings by Subject participated by 1,594 institutions across 54 subjects in 5 broad subject areas are announced today. This year Universiti Teknologi MARA is successfully listed for 13 subjects ranked within 3 broad subject areas namely Social Sciences and Management, Engineering and Technology, and Arts and Humanities. Most notably, UiTM's Art and Design subject finds itself ranked top 240 this year forthe first time in five years since 2017. This success reflects the continuous efforts undertaken by the UiTM College of Creative Arts Studies in delivering excellence to its students. The Vice-Chancellor of UiTM, Professor Ts. Dr. Hjh Roziah Mohd Janor, expressed her delight with the ranking of the Arts and Design subjects this year, along with the remaining twelve subjects that managed to maintain their position in the 2023 QS WUR by Subject. "I would like to congratulate the respective colleges and faculties fortheir hard work and dedication towards improving their academic programmes in delivering the best to our UiTM students. Truly, the efforts have paid off."